THE EFFECT OF FINANCIAL RATIOS AND COMPANY SIZE ON COMPANY VALUE (CASE STUDY ON MANUFACTURING COMPANIES LISTED ON IDX FOR THE 2021-2022 PERIOD) - Rita Novita; Aminah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of the study is to determine how company size, profitability, leverage, and liquidity affect the value of mining subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2021–2022. IBM SPSS Statistics 23 was used to test the data in this quantitative research design. Using purposive sampling techniques, the research sample consisted of 27 companies that met the main criteria of being listed on the Indonesia Stock Exchange in 2021–2022. Multiple linear regression, classical assumption testing, descriptive statistical analysis, and hypothesis testing are the analytical techniques used. Research findings show that in mining subsector manufacturing companies in 2021–2022, profitability, leverage, liquidity, and company size have a considerable positive influence on company value.